Photocatalytic Inactivation of Bacterial Spores using TiO2 Films with Silver Deposits - Zacarias, Silvia Mercedes (2015)
The present work evaluates the enhancement of the photocatalytic inactivation of bacterial spores employing TiO2 films with silver deposits compared to TiO2 films without metal deposition. Bacillus subtilis spores spread over TiO2 films with different silver contents were irradiated with artificial UV-A light. The performances of the coatings were evaluated by the quantum efficiency parameter, which relates the inactivation rate with the radiation absorption rate by the coating. Spectral diffuse transmittance and reflectance measurements of the films were carried out to evaluate the fraction of energy absorbed by the coatings. TiO2 and Ag/TiO2 films characterization also included X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), X-ray photoelectron spectroscopy (XPS), and Scanning Electron Microscopy (SEM). A notable increase in the photocatalytic inactivation was observed by increasing the silver content of the coatings, reaching a maximum quantum efficiency with the sample containing 1.09 wt.% Ag/TiO2. The addition of higher amounts of silver rendered lower inactivation, thus indicating the existence of an optimum Ag/TiO2 relation.